Influence of Storage of Wet Arabica Parchment Prior to Wet Hulling on Moulds Development, OchratoxinA Contamination, and Cup Quality of Mandheling Coffee - Cahya Ismayadi; Anthony Marsh; Renata Clarke (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2005)
Mandheling coffee has been a well known specialty coffees for decades and the demand for this coffee is currently increasing. This coffee is characterised by low acidity, heavy-complex body, spicy-little earthy and fruity flavor. Mandheling coffee is produced by smallholder farmers in the highland surrounding Lake TobaNorth Sumatra in an unique way i.e. following de-pulping and 1–2 days sundrying, wet parchment is stored for varying periods up to a few weeks, the parchments are then de-hulled when still wet (40–45% moisture content) then the beans sundried. The handling procedure presumably contributes to the unique cup character of Mandheling coffee. On the other hand the storage of wet pachments may cause mould growth and mycotoxin contamination. This trial was designed to study the influence of storage of wet parchments prior to wet hulling on mould development, OTA contamination and cup Mandheling characteristic of the coffee product. The normal wet process, drying of parchment thoroughly to 12% moisture content was used as the control. Parchment coffees (6 lots) used for this trial were drawn from farmers and collectors in the region. The wet parchments (41.74–53.96% moisture content) were stored for 1 (D1), 7 (D7) and 14 (D14) days in PE sacks in a warehouse in the region. During the storage period, when there was visible mould growth, the parchments were spread on a plastic sheet inside the warehouse, as per common practice to suppress the mould growth. Following storage, the wet parchment was de-hulled and then sun-dried to a moisture content of 12% (MC12%) or dried to a moisture content of 17%, and held in storage for 3 weeks prior to final drying to 12% mc. The ‘normal wet process’ i.e. fresh-non stored parchments dried thoroughly to 12%, were used as the control. Parameters measured were visual evaluation, mould infestation, a w, moisture content (MC) on the stored parchment; while for dried beans mould infestation, OTA content and the Mandheling cup character evaluation (done by 4 panelists who were familiar to the coffee) were determined. Some mould species grew during the storage course, with black Aspergillus was the dominant species found in the beans, while A. ochraceusan OTA producer, was found in some samples with low infection rate (0–15.3%). Spreading of coffee inside the warehouse during the day could suppress moulds growth. OTA was found in only 5 samples out of 42 samples with range of 0.17–2.24 ppb, very less than European Union limit. There was no clear trend of storage period on the mould infection rates, OTA content, and the Mandheling cup characters. The high variability of the outcome was likely due to the inhomogenity of parchments used for this trial. The best Mandheling was found in the sample of D1-MC12%-coffee source of lot 1. Key words: Mandheling coffee, storage, wet parchment, mould, ochratoxin A.